Severity of erectile dysfunction is highly correlated with the syntax score in patients undergoing coronariography - Weslley Santiago Andrade; Paulo Oliveira; Humberto Laydner; Eduardo Jose Pereira Ferreira; Jose Augusto Soares Barreto Filho (International Brazilian Journal of Urology, 2016)
ABSTRACT Objective To investigate the association between the severity of erectile dysfunction (ED) and coronary artery disease (CAD) in men undergoing coronary angiography for angina or acute myocardial infarct (AMI). Material and Methods We studied 132 males who underwent coronary angiography for first time between January and November 2010. ED severity was assessed by the international index of erectile function (IIEF-5) and CAD severity was assessed by the Syntax score. Patients with CAD (cases) and without CAD (controls) had their IIEF-5 compared. In the group with CAD, their IIEF-5 scores were compared to their Syntax score results. Results We identified 86 patients with and 46 without CAD. The IIEF-5 score of the group without CAD (22.6±0.8) was significantly higher than the group with CAD (12.5±0.5; p<0.0001). In patients without ED, the Syntax score average was 6.3±3.5, while those with moderate or severe ED had a mean Syntax score of 39.0±11.1. After adjustment, ED was independently associated to CAD, with an odds ratio of 40.6 (CI 95%, 14.3-115.3, p<0.0001). The accuracy of the logistic model to correctly identify presence or absence of CAD was 87%, with 92% sensitivity and 78% specificity. The average time that ED was present in patients with CAD was 38.8±2.3 months before coronary symptoms, about twice as high as patients without CAD (18.0±5.1 months). Conclusions ED severity is strongly and independently correlated with CAD complexity, as assessed by the Syntax score in patients undergoing coronariography for evaluation of new onset coronary symptoms.